Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.11646/zootaxa.776.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica

Abstract: Bothriomyrmex paradoxus Dubovikov and Longino sp. nov. is described from Costa Rica, based on two collections from widely separated localities. These are the first collections of the genus Bothriomyrmex in the Americas. The genus Bothriomyrmex can be divided into Palearctic species (Both- riomyrmex s.s.) and Oriental and Australian species, based on differences in palp formula and queen wing venation. Bothriomyrmex paradoxus shares palp and wing characters with the Palearctic species. It is probably native to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“… Wheeler (1915 : 418) described Bothriomyrmex dimmocki based on “two workers, one winged, and four dealate females taken by Dr. George Dimmock August 27, 1897, from a single colony on Mt. Tom, near Springfield, Mass.” Based primarily on the unusually small size of the queens, Wheeler placed the ants in Bothriomyrmex , a genus of temporary social parasites that exploits Tapinoma hosts during colony founding, which was then thought to be exclusively Old World in distribution ( Santschi 1906 ; but see Dubovikoff and Longino 2004 ; Prebus and Lubertazzi 2016 ). Curiously, Wheeler’s description centered on the two workers, which he was at pains to distinguish from those of the Mediterranean Bothriomyrmex meridionalis (Roger).…”
Section: Resultsmentioning
confidence: 99%
“… Wheeler (1915 : 418) described Bothriomyrmex dimmocki based on “two workers, one winged, and four dealate females taken by Dr. George Dimmock August 27, 1897, from a single colony on Mt. Tom, near Springfield, Mass.” Based primarily on the unusually small size of the queens, Wheeler placed the ants in Bothriomyrmex , a genus of temporary social parasites that exploits Tapinoma hosts during colony founding, which was then thought to be exclusively Old World in distribution ( Santschi 1906 ; but see Dubovikoff and Longino 2004 ; Prebus and Lubertazzi 2016 ). Curiously, Wheeler’s description centered on the two workers, which he was at pains to distinguish from those of the Mediterranean Bothriomyrmex meridionalis (Roger).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, these patterns have also been argued to be a product of historic sampling bias for ants in the northern hemisphere (Kutter, 1968; Wilson, 1971, 1984). Fortunately, our knowledge about ant biodiversity in tropical regions has made significant progress in recent decades (see for example: Delabie et al, 2015; Fernández, 2003; Fernández et al, 2019; Fisher & Bolton, 2016; Shattuck, 2000), and simultaneously numerous ant social parasite species were discovered in tropical and subtropical regions (Bharti, Radchenko, et al, 2016; Blaimer, 2012a; De Souza et al, 2007; Dubovikoff & Longino, 2004; Feitosa et al, 2008; Fischer et al, 2020; Guerrero et al, 2010; Longino, 2003, 2006, 2007; Messer et al, 2020; Prebus & Lubertazzi, 2016; Rabeling & Bacci, 2010; Rabeling et al, 2015, 2019; Schultz et al, 1998). In fact, reviewing taxonomic studies including ant social parasites showed that the majority of newly discovered ant social parasites in the past two decades were described from the Neotropics (Appendix S1, Fig.…”
Section: Introductionmentioning
confidence: 99%